การเปรียบเทียบประสิทธิภาพการจำแนกกลุ่มการสำเร็จการศึกษาภายในสองปีและมากกว่าสองปีการศึกษาของนักศึกษาระดับปริญญามหาบัณฑิต คณะวิทยาศาสตร์ สถาบันเทคโนโลยีพระจอมเกล้าเจ้าคุณทหารลาดกระบัง - พรมนาง นภาพร; สินสมบูรณ์ทอง สายชล (Thai Journal of Science and Technology, 2020)
In this research, a comparative study of classifying efficiency in factors affecting the completion of master degree programs in the faculty of Science, King Mongkut’s Institute of Technology Ladkrabang was investigated in the academic year 2014-2018. The samples were drawn via stratified simple random sampling method, and the obtained data were analyzed using binary logistic regression and discriminant model and considered the percentage in the average accuracy classification. By the discriminant analysis, the percentages of accuracy classification in completion of master degree programs within two years (group 1), and more than two years (group 2) were 94.74 and 87.5 %, respectively, with the average of 89.55 %. These were higher than those by binary logistic regression analysis, which the percentages of accuracy classification were 81.58 and 82.29 %, respectively, with the average of and 82.09 %. The graduated faculty, studying time, studying performance, research methodology perception, and relationship between thesis advisor and student, were five independent variables, which significantly affected learning achievement of the graduates in the faculty of Science, by using equation